Nectomys squamipes como hospedeiros de manutenção de leptospiras patogênicas no Vale do Rio Paranaíba, estados Goiás e Minas Gerais, Brasil - Moreia, R. Q.; Ramos, V. N.; Vieira, R. F.; Pires, B. C.; Libonati, H.; Lilenbaum, W.; Lima, A. M. C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a disease that occurs more frequently in regions of tropical climate, which favor the survival of the bacteria in the environment. Nectomys squamipes is a wild rodent of semiaquatic behavior, which favors its contact with leptospires.